Pengaruh Pendapatan Asli Daerah, Belanja Daerah, dan Kompleksitas Pemerintahan terhadap Transparansi Informasi Keuangan Daerah Via Website - Sophi Dezalinda; Mayar Afriyenti (Universitas Negeri Padang, 2024)
The aim of this study is to offer actual data on the impact of local income, regional spending, and governmental complexity on the accessibility of regional financial data online in Indonesia. Based on the accessibility of acquiring regional financial information with three years of research observation, this study looks at the transparency of financial information on government websites in 34 Indonesian provinces. Multiple linear regression analysis was used to test this study. The research's conclusions indicate that local original income significantly improves the accessibility of regional financial data on websites. However, regional expenditure variables and government complexity have no influence on the transparency of regional financial information via the website. This result supports the signal theory, which holds that a high level of local revenue signifies that the government is successfully discharging its obligations to the community. The results of this study can be utilized by local governments to establish internal or external laws, improving the transparency of financial data on local government websites going forward.